Pengembangan LKPD Berbasis Coding Robotik dengan Pendekatan STEM untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMP - Roufatul Mucharromah; Pramudya Dwi Aristya Putra (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study was conducted to develop a student worksheet (LKPD) based on robotic coding that integrates STEM to enhance the critical thinking skills of junior high school students in science lessons. Students' critical thinking skills were low because learning methods were still dominated by teacher-led lectures, alongside a lack of interactive teaching materials that foster active student engagement. Furthermore, students had not previously been introduced to STEM-focused learning or robotic coding, resulting in limited abilities regarding analysis, problem-solving, and understanding concepts of motion. This study employed the Research and Development (R&D) method, specifically the ADDIE development model. The research took place at SMP Negeri 2 Jember, located at Jalan PB Sudirman No. 26, Kp. Using, Jemberlor, Patrang District, Jember Regency. The research subjects were 36 students from class VII E at SMP Negeri 2 Jember during the 2025/2026 academic year. Data collection instruments included expert validation sheets, lesson implementation observation sheets, pre-tests and post-tests, and student response questionnaires. Research findings indicate that the robotic coding-based student worksheet utilizing a STEM approach achieved an average validity score of 88.6%, classifying it as "highly valid." Regarding practicality, the worksheet obtained an overall score of 85.56%, indicating it was "highly practical." Effectiveness results, based on N-Gain analysis, yielded an overall score of 0.45 (medium category), while student response questionnaires fell into the "very good" category with a score of 84.06%. Based on these results, the robotic coding-based student worksheet with a STEM approach is deemed valid, practical, and effective for enhancing junior high school students' critical thinking skills regarding the topic of motion.